Rare diagnosis of an Epstein-Barr virus-positive extracavitary/solid variant of primary effusion lymphoma by duodenal endoscopic biopsy in a human immunodeficiency virus-seronegative and immunocompetent patient: A case report - Beril Guler; Guven Cetin (Indian Journal of Pathology and Microbiology)
Primary effusion lymphoma and its tissue-based subtype extracavitary/solid variant was first described in human immunodeficiency virus (HIV)-seropositive patients. We report the case of a 50-year-old HIV-seronegative male patient who presented with icterus and cholestasis. Computed tomography revealed a 80 × 56 mm abdominal mass. Fine-needle aspiration biopsy was performed from the celiac lymph nodes and pancreatic head, under endoscopic ultrasonography guidance. A duodenal endoscopic biopsy was taken from the infiltration area, and a core biopsy was performed for the portal hilar mass. All biopsies showed similar cytohistopathological features. LCA-positive lymphoid neoplasia had a plasmacytoid/anaplastic morphology and null cell phenotype. HHV-8 and Epstein-Barr virus-encoded small RNAs (EBER) were diffuse positive. The patient, who did not have an effusion, was diagnosed with an extracavitary/solid variant of primary effusion lymphoma. Virus-associated lymphoproliferative disorders should be considered in the differential diagnosis of patients without a history of immunosuppression or HIV infection.